(untitled) (Journal of Face Aesthetics, 2022)
Taking care of the external appearance, and in particular the face, has been and is a phenomenon that binds society bonding in everyday and cultural life. Body decoration, including the face, falls under the categories of modification of the so‑called transforming and can take many forms. The article discusses the phenomenon of face modification and its symbolic meaning on the examples of tattoos (Polynesian „moka”, Japanese „kanji inu”) piercing (Murs tribe), scarification (tribal scars) as well as extreme forms of modification („bagel head”).